CFD modelling of an indirectly heated calciner reactor, utilized for CO2 capture, in an Eulerian framework. (15th August 2023) - Kanellis, Georgios; Zeneli, Myrto; Nikolopoulos, Nikolaos; Hofmann, Carina; Ströhle, Jochen; Karellas, Sotirios; Konttinen, Jukka
Abstract: This study focuses for the first time on the transient three-dimensional CFD simulation of the novel bubbling-bed calciner of an indirectly heated calcium looping pilot plant. The granular flow in the calciner is modelled according to the state-of-the-art Eulerian–Eulerian (Two Fluid Model — TFM) approach. To take into account flow heterogeneity aspects, the drag coefficient is modelled applying the sub-grid energy-minimization multiscale (EMMS) scheme, customized for the specific operating conditions. For the calcination kinetics a changing grain size model (CGSM) from Labiano et al. is used. An important advancement of the current approach lies on the consideration of all the related heat transfer mechanisms from the heat pipes towards the bubbling bed, i.e., both convection and radiation are considered. The simulation results are verified against data measurements obtained from an experimental campaign performed at Technische Universität Darmstadt. The CFD model provides an accurate pressure profile along the calciner height, having a maximum difference of 15 mbar (12% of the total experimental pressure drop) with the experiments. In addition, the CO2 mass fraction at the outlet is successfully predicted with an error of only 3%. Concerning the heat flux, a mesh independent solution with computationally affordable grid size was not possible due to the thin thermal boundary layer, which has also been reported in all relevant research. Nevertheless, the provided solution was found to be almost mesh independent hydrodynamically. For this reason, an estimation of the heat transfer coefficient of the heat pipe heat exchanger was made by using several 0-D mechanistic models, which take as input hydrodynamic data obtained from CFD. As a follow-up, the CFD model combined with the empirical heat transfer correlations is indicatively used to parametrically investigate the effect of fluidization velocity on the heat transfer coefficient of the heat pipe heat exchanger. Through this study, this paper sheds important light on the effect of hydrodynamics on the radiative and convective components of heat transfer. It is shown that a 20% change in fluidization velocity will mildly (¡2%) affect the total heat flux, due to its counterbalancing effect on the radiative and convective components. Highlights: CFD model development for the calciner of a novel 300 MWth IHCaL pilot plant. The model is validated against experimental data. HTC is calculated from empirical 0-D models with CFD data as input. Radiation accounts for 20%–30% of the total heat flux. Parametric investigation of fluidization velocity on HTC.